Pengaruh Kompensasi dan Lingkungan Kerja terhadap Retensi Karyawan melalui Employee Engagement sebagai Variabel Mediasi pada PT Jaya Abadi Solution - Azkiyatul Fadzrin; Kasnowo Kasnowo; Rini Armin (Indo Publishing, 2026)
This study examines the direct and indirect effects of Compensation and Work Environment on Employee Retention, with Employee Engagement as a mediating variable at PT Jaya Abadi Solution, a livestock feed manufacturer in Mojokerto, East Java. The study was motivated by a rising employee turnover trend from 10% in 2021 to 18% in 2025, exceeding the ideal industry threshold of 10%, despite the company's ceremonial retention efforts. A quantitative causal approach was applied to the entire population of 135 active employees using a saturated sampling (census) technique. Primary data were collected through a structured Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that Compensation and Work Environment each have a positive and significant direct effect on Employee Retention and on Employee Engagement, and that Employee Engagement significantly mediates both relationships as a partial mediator. The structural model explains 75.0% of the variance in Employee Retention and 65.5% of the variance in Employee Engagement. These findings suggest that management should strengthen compensation fairness and workplace comfort simultaneously with efforts to build employees' emotional engagement in order to reduce turnover sustainably.